Development of Material Teaching of Pencak Silat in Physical Education Classes for 8-12 Years Old in Elementary School (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
Pencak silat is a new material in the Physical Education subject in Elementary Schools. The existence of pencak silat material in the upper grades of elementary school as a new material makes the need for pencak silat teaching materials become important. There is no material whose contents include pencak silat material that must be mastered by students in accordance with basic competencies at the elementary school level for the upper class. This study aims to develop a product of pencak silat teaching materials that can be implemented in the subjects of physical education in the upper grades of the elementary school. The research method used is Research & Development. This research instrument uses a questionnaire. The research subjects in this study are teaching materials experts, pencak silat experts, physical education teachers, and students. The result of the research is a product of developing pencak silat teaching materials for the upper class in elementary schools. The results of the expert evaluation on the initial product draft were 81.8% in the